2020
DOI: 10.1057/s41299-020-00107-z
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Celebrity Trust and Its Effects on Other Credibility and Image Constructs: A Qualitative Approach

Abstract: Foroudi, Pantea ORCID: https://orcid.org/0000-0003-4000-7023 and Yousef, Waleed (2020) Understanding celebrity trust and its effects on other credibility and image constructs: a qualitative approach. Corporate Reputation Review .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 115 publications
0
9
0
Order By: Relevance
“…Many studies on celebrity endorsement emphasise the vital role of trust in conveying the message (Ismagilova et al , 2020; Lou and Yuan, 2019). In the celebrity endorsement context, trustworthiness towards the celebrity is often described as the extent to which the audience views the celebrity to be capable of conveying a feeling of integrity, honesty and credibility through the message generated via a marketing medium (Hussain et al , 2020; Wang and Scheinbaum, 2018). Moreover, current literature suggests that trustworthiness towards the celebrity is linked to a more positive attitude towards the message shared (Wang and Scheinbaum, 2018).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Many studies on celebrity endorsement emphasise the vital role of trust in conveying the message (Ismagilova et al , 2020; Lou and Yuan, 2019). In the celebrity endorsement context, trustworthiness towards the celebrity is often described as the extent to which the audience views the celebrity to be capable of conveying a feeling of integrity, honesty and credibility through the message generated via a marketing medium (Hussain et al , 2020; Wang and Scheinbaum, 2018). Moreover, current literature suggests that trustworthiness towards the celebrity is linked to a more positive attitude towards the message shared (Wang and Scheinbaum, 2018).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…, 2011). Celebrity trust also emits positive signals to build brand credibility and image, which further develops corporate credibility and corporate image (Hussain et al. , 2021).…”
Section: Review Of Literaturementioning
confidence: 99%
“…These communications signal investors regarding companies' involvement in positioning brands, improving profitability and cash flows, and the firm's financial strength (Clark et al, 2002;Ding et al, 2011). Celebrity trust also emits positive signals to build brand credibility and image, which further develops corporate credibility and corporate image (Hussain et al, 2021).…”
Section: Stock Investment Intentionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Han and Ki (2010) found that celebrity reputation represents six dimensions, i.e., personalities, relationships, appearance, expert abilities, management of their private lives, and reputation. For many years, corporations have learned how to use celebrities' reputations to promote credibility (Hussain et al, 2021). Goldsmith et al (2000) reported that celebrity credibility has the strongest impact on consumers' attitudes toward the ad, while corporate credibility has the strongest impact on consumers' attitudes toward the brand.…”
Section: Celebritymentioning
confidence: 99%